1998
DOI: 10.1677/jme.0.0200175
|View full text |Cite
|
Sign up to set email alerts
|

Is prolactin a gonadotrophic hormone in red deer (Cervus elaphus)? Pattern of expression of the prolactin receptor gene in the testis and epididymis

Abstract: This study investigated the pattern and site of expression of the prolactin receptor gene in the testis and epididymis of red deer collected during the breeding season (n=3). Ribonuclease protection assays using 50 µg total RNA and a 300 bp [ 32 P]-labelled antisense cRNA probe, generated from the extracellular domain of the red deer prolactin receptor, confirmed the expression of the receptor in both the testis and epididymis; a higher level of prolactin receptor mRNA was detected in the epididymis compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…PRLR expression has been reported in a wide variety of cells and tissues. In male, PRLR was expressed in the testes and in various male accessory glands include vas deferens, epididymis, prostates and seminal vesicles 11 13 31 , which demonstrated that these organs might be direct targets of PRL, suggesting multiple regulatory roles for PRL in male reproductive tract. The present study demonstrated for the first time the expression of the PRLR gene and protein in the scented glands of the male muskrats during the breeding and nonbreeding seasons.…”
Section: Discussionmentioning
confidence: 96%
“…PRLR expression has been reported in a wide variety of cells and tissues. In male, PRLR was expressed in the testes and in various male accessory glands include vas deferens, epididymis, prostates and seminal vesicles 11 13 31 , which demonstrated that these organs might be direct targets of PRL, suggesting multiple regulatory roles for PRL in male reproductive tract. The present study demonstrated for the first time the expression of the PRLR gene and protein in the scented glands of the male muskrats during the breeding and nonbreeding seasons.…”
Section: Discussionmentioning
confidence: 96%
“…In a report on bears, prolactin increased the LH receptor expression level in the testis [ 22 ], suggesting that prolactin is also involved in activation of the gonadal function in horses by stimulating LH receptor expression in the gonads and increasing LH sensitivity. The expression of prolactin receptor has been reported in the testes and various male accessory glands [ 18 , 20 , 24 ], indicating that these organs are targets of prolactin in male reproductive organs. Previous studies have also demonstrated the expression of testicular prolactin receptor increased during testicular recrudescence in the breeding season [ 6 , 22 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In all species studied, PRL acts by binding to a specific membrane receptor (PRL-R) (Clarke et al 1997;Jabbour et al 1998;Ohkubo et al 1998;Howell-Skalla et al 2000;Sandra et al 2000;Higashimoto et al 2001). Two main forms of PRL-R transcript have been identified (BoleFeysot et al 1998), one of which is specific for a short form of receptor (Boutin et al 1988), while the other is specific for a long form whose molecule possesses a cytoplasmic tail (Boutin et al 1988;Shirota et al 1990).…”
Section: Introductionmentioning
confidence: 99%